Trade-offs in the design of multimodal interaction for older adults. Issue 5 (4th April 2022) - Schiavo, Gianluca; Mich, Ornella; Ferron, Michela; Mana, Nadia
ABSTRACT: This paper presents key aspects that designers and Human–Computer Interaction practitioners might encounter when designing multimodal interaction for older adults, focusing on the trade-offs that might occur as part of the design process. The paper gathers literature on multimodal interaction and assistive technology, and describes a set of design challenges specific for older users. Building on these main design challenges, four trade-offs in the design of multimodal technology for this target group are presented and discussed. To highlight the relevance of the trade-offs in the design process of multimodal technology for older adults, two of the four reported trade-offs are illustrated with two user studies that investigate mid-air and speech-based interaction with a tablet device. The first study explores the design trade-offs related to redundant multimodal commands in older, middle-aged and younger adults, whereas the second one investigates the design choices related to the definition of a set of mid-air one-hand gestures and voice input commands for older adults. Further reflections highlight the design trade-offs that such considerations bring in the process, providing an overview of the design choices involved and of their potential consequences.